A critical study on the duty to refer in the light of traditional and Complementary Medicine Act 2013 / Afiifah Shariha Mohd Supi … [et al.] - Mohd Supi, Afiifah Shariha; Mhd Redza, Nora Amina Fahsya; Kamarudzaman, Nurul Azawani; Aminuddin, Zahratunnur Hanim Ajla (Faculty of Law, 2014)
This research has been conducted to analyse the existing legal framework in Malaysia governing the traditional and complementary medicine practice. The research aims to analyse the inadequacy of the law of traditional and complementary medicine in Malaysia specifically in the Traditional and Complementary Medicine Act (TCMA) 2013 (the Act). The main concern of this research is the issue on the suitable standard of duty of care specifically duty to refer of TCM practitioner in light of section 30 of TCMA 2013. Section 30(1) of the Act imposed the obligation to the practitioners for referring their patient in two situations. The first situation is where the TCM practitioner need to refer patient to the medical practitioner if the patient experiencing an acute medical emergency and second, where the ailment or condition of the patient is beyond the skill, competency or their expertise of the TCM practitioner. Failure to comply, the practitioners shall be liable for breach of duty and may be subjected to penalty or if the patient wish, he may bring the case to the court. The focus shall be given to the action where the patient may bring the case of breaching the duty of care to court. Therefore, the researchers will highlight the suitable standard of care and approaches to be used in court. Different cases such as Bolitho v City & Hackney Health Authority, Abdul Rahman bin Abdul Karim v Abdul Wahab bin Abdul Hamid, etc shall be referred to.